Targeting ferroptosis in pemphigus vulgaris using aptamer-modified extracellular vesicles - Yishu Tang; Yuxuan Zhang; Hongli Ding; Hao Jin; Liang Zhang; Mao Luo; Keyan Chen; Bin Wei (Chemical Engineering Journal, 2025)

Overexpression of long non‑coding RNA H19 enhances cell viability and inhibits apoptosis in recurrent spontaneous abortion by targeting the miR-29a-3p/SOCS3 axis - Zhengli Qian; Keyan Luo; Mingzhe Zhang; Dejing Wang; Yu Hu; Qinghan Li (In Vitro Cellular & Developmental Biology - Animal, 2025)

The biodegradation pathway of HBCDs in the enriched microbial community - Bing Zhang; Wenqi Luo; Yongjin Liu; Haonan Chen; Tiantian Pan; Baole Wang; Keyan Li; Huaqing Jia; Shirou Zhou; Shanshan Meng; Xueying Ye; Tao Peng; et al. (International Biodeterioration & Biodegradation, 2025)

Recent progress of Clostridium butyricum in fish culture: Maintenance of intestinal homeostasis, improvement of disease resistance, activation of immune signaling pathways, and positive effects on fish - Keyan Cai; Jingyi Chen; Zhepeng Zhang; Yawen Ye; Shangyuan Sang; Xiaohu Luo; Yajun Wang; Kai Shan; Changrong Ou; Ling-ling Jia (Aquaculture, 2025)

Influence of different tectonic settings on fracture formation and fluid flow around upper-crustal magmatic intrusion: insights from numerical modelling - Cheng Chang; Keyan Xiao; Gang Luo; Li Sun (Earth Science Informatics, 2024)
Large porphyry Cu and epithermal Au deposits tend to form in distinct tectonic, porphyry and high-sulfidation epithermal deposits in compressional settings, and low-sulfidation epithermal deposits in extensional settings. Given that the analysis of the shallow metallogenic dynamic processes at the upper-crust scale is insufficient, especially the ore-bearing fracture formation and fluid-focusing mechanism around the mineralizing magmatic intrusion under different tectonic backgrounds, we aimed to study how tectonic settings influence fracture formation and fluid hydrodynamics in and around a hot intrusion. We developed a finite element model coupling thermal-hydrological-mechanical processes to simulate the fracture formation, evolution of fluid velocities, and accumulation of water-rock interactions. The model results show that tectonic compression increases the degree of fracturing, hydrothermal fluid velocities, and water-rock interaction within and laterally around the intrusion; tectonic extension enhances fracturing, hydrothermal fluid velocities, and water-rock interaction at shallow depth. These results confirm that tectonic compression may promote the formation of porphyry Cu deposits, while tectonic extension may promote the formation of shallow hydrothermal deposits. Our model explains the effects of tectonic activity on fracture formation and fluid flow around hot magmatic intrusions in upper crust and deepens our understanding of the relationship between tectonic activity and deposit formation there.

Detection and quantification of cotton trichomes by deep learning algorithm - Keyan Luo; Yu Jin; Shuhan Wen; Yicheng Li; Junkang Rong; Mingquan Ding (Computers and Electronics in Agriculture, 2023)